Correlation Between Pull-Out Strength And Insertion Strain Field In Relation To Bone Screw Insertion Angle - Zulkifle, Muhammad Syamim (Universiti Sains Malaysia, 2021)
In this final year project, an investigation of the correlation between pull-out strength and insertion strain field in relation to bone screw insertion angle is studied. In general, cortical screw is one of the internal fixation devices that surgeons used to perform orthopedic surgery however, studies have found that the use of these devices may cause hardware loosening. Many studies have come out with several solutions which are changing the screw material and alter the screw insertion depth. However, this study will explain on how the screw insertion angle influences the pull-out force of the screw as the strain field developed within the bone, and the affects the pull-out force. A cortical screw and 0.32 g/cm3 rigid PU foam block are the main material for this experiment. There are two experiments conducted which are the Screw Insertion and Screw Pull-out Test that will be done according to the ASTM standards. In screw insertion test, screw insertion strain developed within the PU foam block are analyzed using Digital Image Correlation (DIC) system and Davis 10 software. While in screw pull-out test, the pull-out strength is analyzed and calculated using a specialized software with the UTM Instron 8874. The results show that the maximum recorded screw pull-out force is 607.43 N when the screw is inserted at 30⁰, the highest strain displacement in x and y direction is 0.0115 at 15⁰ screw insertion and 0.025 at 0⁰ screw insertion, respectively.